Mental Health of Rhinoplasty Applicants: A Case Control Study - Oveis Mehriar; Farhad Asghari; Shadman Nemati; Abbas Sadeghi; Ali Faghih Habibi; Ghasem Salehpoor (Journal of Holistic Nursing and Midwifery)
Introduction: Rhinoplasty applicants seem to be more susceptible to psychosomatic problems compared to other cosmetic surgery groups and this can affect their decision to go in for surgery. Objective: This study aims to determine the mental health of two groups—the control group and the group of rhinoplasty applicants—before surgery, based on their gender. Materials and Methods: This case control study was conducted in 2013 at a Hospital of Rasht. A total of 136 rhinoplasty applicants and 136 individuals as the control were selected, using the availability sampling method, and investigated through a checklist of symptoms of the disease (Symptom Check List-90-Revised). The data analysis was performed using the one-variable and multivariate covariance analyses. Results: The main effect of grouping showed that rhinoplasty applicants had significantly higher mean scores than the control group in the interaction sensitivity components (P = 0.017) and anxiety (P = 0.009). In this case, the main effect of gender and the interactive effect of group and gender were not significant in any aspect of mental health. Conclusion: Poor mental health among volunteers of cosmetic surgery can be one of the factors behind their tendency toward such surgeries, including rhinoplasty. Therefore, investigation, assessment, and psychological intervention are recommended for these applicants before surgery to improve the image of him or herself as a person and reduce the symptoms of negative psychosis.